DIFFERENCES IN THE AMPLITUDE OF ACCOMMODATION BETWEEN CHILDREN WITHOUT DEVELOPMENTAL DISABILITIES AND CHILDREN WITH DEVELOPMENTAL DISABILITIES - Karim, Muhammad Rico Abdul; Wulandari, Lely Retno; Dewi, Nadia Artha; Anandita, Nanda Wahyu (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Accommodation is the eye's ability to change the refractive power of the lens, allowing objects to focus on the retina at different distances. The Amplitude of Accommodation (AoA) is the closest point at which the eye can focus and the distance between the far point and near point on the diopter scale. Children with developmental disabilities (CDD) are at a higher risk of encountering vision problems, including accommodation issues. Objective: This study aims to ascertain the disparity in Amplitude of Accommodation (AoA) results between children with developmental disabilities (CDD) and those without developmental disabilities (CWDD) Methods: This research constitutes an observational study with cross-sectional data, involving 44 subjects with developmental disabilities (CDD) and 44 subjects without developmental disabilities (CWDD). The participants were further categorized into 33 deaf children (DC) and 11 children with intellectual disabilities (CID). The data were obtained from eye examinations conducted at several special schools and orphanages in the city of Malang. The examinations covered the right eye (OD), left eye (OS), and binocular vision (ODS). Results: Significant differences were identified among groups in OD (P<0.001), OS (P<0.001), and ODS (P<0.001). To assess the specific variations between groups, a Bonferroni post-hoc test was conducted. The results indicated significant differences between CWDD and DC in both OD (P<0.001), OS (P<0.001), and ODS (P<0.001). Additionally, significant differences were observed between CWDD and CID in OD (P=0.002), OS (P=0.005), and ODS (P<0.001). Conclusion: It can be concluded that there is a significant difference in the average AoA value between CWDD and CDD, both CWDD-DC and CWDD-CID.